An Interface-Directed Coassembly Approach To Synthesize Uniform Large-Pore Mesoporous Silica Spheres - Wang, Minghong; Sun, Zhenkun; Yue, Qin; Yang, Jie; Wang, Xiqing; Deng, Yonghui; Yu, Chengzhong; Zhao, Dongyuan (Journal of the American Chemical Society, 2014)
A facile and controllable interface-directed coassembly (IDCA) approach is developed for the first time to synthesize uniform discrete mesoporous silica particles with a large pore size (ca. 8 nm) by using 3-dimensional macroporous carbon (3DOMC) as the nanoreactor for the confined coassembly of template molecules and silica source. By controlling the amount of the precursor solution and using Pluronic templates with different compositions, we can synthesize mesoporous silica particles with diverse morphologies (spheres, hollow spheres, and hemispheres) and different mesostructure (e.g., 2-D hexagonal and 3D face centered cubic symmetry), high surface area of about 790 m2/g, and large pore volume (0.98 cm3/g). The particle size can be tunable from submicrometer to micrometer regimes by changing the macropore diameter of 3DOMC. Importantly, this synthesis concept can be extended to fabricate multifunctional mesoporous composite spheres with a magnetic core and a mesoporous silica shell, large saturated magnetization (23.5 emu/g), and high surface area (280 m2/g). With the use of the magnetic mesoporous silica spheres as a magnetically recyclable absorbent, a fast and efficient removal of microcystin from water is achieved, and they can be recycled for 10 times without a significant decrease of removal efficiency for microcystin.